2016
DOI: 10.12714/egejfas.2016.33.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Determination of shelf life of Gibel Carp (Carassius gibelio, Bloch 1782) marinades in different sauces stored at 4 ºC

Abstract: In this study, quality properties and shelf life for gibel carp (Carassius gibelio, Bloch 1782) marinades during stored at 4±1 °C in different sauces was investigated. The marinating process was carried out in 2.5% vinegar, 10% salt and water for 72h at 4±1 °C. After the marination process, fish were removed from the solutions, transferred in to glass jar contain with different sauces (Group A: sunflower oil and tomato paste, Group B: sunflower oil with garlic, red pepper, thyme, basil and mint and the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…In two marinate groups, the amount of acidity in fish meat decreased with time. This situation paralleled with the pH findings obtained in the study and was found to be compatible with previous study (Maktabi et al, ; Patır et al, ; Taşkaya et al, ).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In two marinate groups, the amount of acidity in fish meat decreased with time. This situation paralleled with the pH findings obtained in the study and was found to be compatible with previous study (Maktabi et al, ; Patır et al, ; Taşkaya et al, ).…”
Section: Resultssupporting
confidence: 94%
“…Some researchers have reported that in such products the pH is between 4.1 and 4.5 and should not exceed 4.5 (Çelik, ; Duyar & Eke, ; Kilinc & Cakli, ; Ludorff & Meyer, ). The marination studies with different fish species and techniques are also consistent with ours with the low pH results after marination (Çelik, ; Erkan et al, ; İnanlı, Özpolat, Çoban, & Karaton, ; Maktabi, Zarei, & Chadorbaf, ; Patır et al, ; Taşkaya, Alparslan, Hasanhocaoğlu Yapıcı, Metin, & Baygar, ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The shelf-life studies help food processors, and handlers determine quality changes during storage and transportation. The shelf-life determination of sauces is limited since most studies have been done on oriental sauces (Lee et al, 2015;Taşkaya et al, 2016;Kim et al, 2018;Kim et al, 2019). The objective of this study was to determine the physical, chemical, sensory, and microbiological changes in the quality characteristics of five developed Americanstyle chicken wing sauces during real-time ambient shelf storage.…”
Section: Introductionmentioning
confidence: 99%